Answer:
Be more productive
Step-by-step explanation:
This could be a goal
D = sqrt (x2 - x1)^2 + (y2 - y1)^2
(1,-2)(10.-4)
d = sqrt (10 - 1)^2 + (-4 - (-2)^2
d = sqrt (9^2 + (-4 + 2)^2
d = sqrt (9^2 + (-2^2)
d = sqrt (81 + 4)
d = sqrt 85
d = 9.2
Answer:
Solve the equation for x by finding a
, b
, and c of the quadratic then applying the quadratic formula.
Step-by-step explanation:
Exact Form:
x = -5±√
5/2
Decimal Form:
x = −
1.38196601
…
, −
3.61803398
…
Answer:
Well what do you need help on. :) Ill be happy to help.
Step-by-step explanation:
Answer:
I think
Step-by-step explanation:
I think its 3 ^7 but i could be wronf